Postbiotics: The concept and their use in healthy populations - Vinderola, Gabriel; Sanders, Mary Ellen; Salminen, Seppo; Szajewska, Hania (Frontiers in Nutrition, 2022)
The term postbiotic was recently defined by an international panel of scientists convened by the International Scientific Association of Probiotics and Prebiotics as “a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host”. This definition focused on the progenitor microbial cell or cell fragments, not just metabolites, proteins or carbohydrates they might produce. Although such microbe-produced constituents may be functional ingredients of the preparation, they are not required to be present in a postbiotic according to this definition. In this context, terms previously used such as paraprobiotics, ghostbiotics, heat-inactivated probiotics, non-viable probiotics, cell fragments or cell lysates, among others, align with the term postbiotics as conceived by this definition. The applications of postbiotics to infant nutrition and pediatric and adult gastroenterology, mainly, are under development. Some applications for skin health are also underway. As postbiotics are composed of inanimate microorganisms, they cannot colonize the host. However, they can in theory modify the composition or functions of the host microbiota, although evidence for this is scarce. Clinical results are promissory, but, overall, there is limited evidence for postbiotics in healthy populations. For example, postbiotics have been studied in fermented infant formulas. The regulation of the term postbiotic is still in its infancy, as no government or international agency around the world has yet incorporated this term in their regulation.